2013
DOI: 10.1089/aid.2013.0122
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics in HIV Prevention; Current Status and Future Directions: A Summary of the DAIDS and BMGF Sponsored Think Tank on Pharmacokinetics (PK)/Pharmacodynamics (PD) in HIV Prevention

Abstract: Thirty years after its beginning, the HIV/AIDS epidemic is still raging around the world. According to UNAIDS, in 2011 alone 1.7M deaths were attributable to AIDS, and 2.5M people were newly infected by the virus. Despite the success in treating HIV-infected people with potent antiretroviral drugs, preventing HIV infection is the key to ending the epidemic. Recently, the efficacy of topical and systemic antiviral chemoprophylaxis (i.e., preexposure prophylaxis or "PrEP"), using the same drugs used for HIV trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 42 publications
2
37
0
Order By: Relevance
“…One small study successfully reduced the dose of efavirenz in patients with the CYP2B6 516 G→T polymorphism using adjunctive TDM [64]. The CYP2B6 516 G→T polymorphism is particularly prevalent in Black African and African American populations (up to 20%), and PK studies have demonstrated higher exposure in these populations [65].…”
Section: Pharmacogenomics To Identify/ Minimize Toxicitymentioning
confidence: 99%
“…One small study successfully reduced the dose of efavirenz in patients with the CYP2B6 516 G→T polymorphism using adjunctive TDM [64]. The CYP2B6 516 G→T polymorphism is particularly prevalent in Black African and African American populations (up to 20%), and PK studies have demonstrated higher exposure in these populations [65].…”
Section: Pharmacogenomics To Identify/ Minimize Toxicitymentioning
confidence: 99%
“…6A for PCL-based NPs [11,14]. These differences may be explained by HIV transmission [65], namely in the case of dapivirine [66]. 665 Results for cell monolayer retention (Fig.…”
mentioning
confidence: 98%
“…Most microbicide products developed and tested so 61 far in human clinical trials have relied in semi-solid dosage forms, 62 particularly gels. These are coitally-dependent systems (i.e., require 63 administration shortly before/after intercourse) that frequently 64 lead to poor user adherence and, thus, potentially reduced ability 65 to protect against transmission [3]. However, modified and sus- 66 tained drug delivery systems, such as vaginal rings, may be prefer- 67 able and are receiving a lot of the current attention as these can 68 provide coitally-independent options for protection [4].…”
mentioning
confidence: 99%
“…Genital fluid concentrations of raltegravir are higher than plasma concentrations, an attractive quality for a PrEP agent (8,9). However, no studies have examined intracellular tissue concentrations of raltegravir in the genital tract, where the level of the drug would be critical to ensuring efficacy (10). Raltegravir is a substrate for P glycoprotein transporter, which is expressed in cervical tissue (11) and is partially regulated by progesterone (12,13), and thus intracellular concentrations could vary throughout the menstrual cycle.…”
mentioning
confidence: 99%